Jenayah Siber Kehartaan Di Malaysia Menurut Hukum Islam: Analisis Isu Terpilih: Wealth Cybercrime in Malaysia from Islamic Law Perspective: Selected Issues Analysis - Ahmad Termimi, Muhamad Asyraf; Ramli, Rushdi (Online Journal of Research in Islamic Studies, 2017)
Advances of information and communications technology nowadays has created a borderless world where information and dealings can be solved at the fingertips by using electronic devices and internet connections. Nevertheless, not all of these facilities and advancements are best utilized by the users as there are some irresponsible who take the opportunity to abuse the crime. Cybercrime is a common issue which was discuss nowadays as it happens all over the world and is no exception for Malaysia. This article discusses the modus operandi three forms of cybercrime: hacking, scamming and phishing and the current legal analysis of the crime. The study found that there was an important foundation that needed to exist before the convocation of each the crime of malicious elements and the encroachment on controlled property.